2023
DOI: 10.1101/2023.02.23.529616
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MAP9/MAPH-9 supports axonemal microtubule doublets and modulates motor movement

Abstract: Microtubule doublets (MTDs) are a well conserved compound microtubule structure found primarily in cilia. However, the mechanisms by which MTDs form and are maintained in vivo remain poorly understood. Here, we characterize microtubule-associated protein 9 (MAP9) as a novel MTD-associated protein. We demonstrate that C. elegans MAPH-9, a MAP9 homolog, is present during MTD assembly and localizes exclusively to MTDs, a preference that is in part mediated by tubulin polyglutamylation. Loss of MAPH-9 caused ultra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…In contrast, there was no abnormal extension of ciliary axoneme in the MAP9 aff -overexpressing cells ( Figures 7A, B ). Based on these results and other evidence showing a relationship between MAP9 and MT ( Venoux et al, 2008 ; Tran et al, 2023 ), the MAP9 wt protein may play an important role in the formation and stabilization of ciliary axonemes. Meanwhile, the MAP9 aff protein has obviously different properties from MAP9 wt and may be deprived of critical roles in cilia stabilization.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…In contrast, there was no abnormal extension of ciliary axoneme in the MAP9 aff -overexpressing cells ( Figures 7A, B ). Based on these results and other evidence showing a relationship between MAP9 and MT ( Venoux et al, 2008 ; Tran et al, 2023 ), the MAP9 wt protein may play an important role in the formation and stabilization of ciliary axonemes. Meanwhile, the MAP9 aff protein has obviously different properties from MAP9 wt and may be deprived of critical roles in cilia stabilization.…”
Section: Resultssupporting
confidence: 66%
“…Others have shown that endogenous MAP9 is strongly expressed in the centrosomal MT asters and the central spindle during mitosis in mammalian cells ( Saffin et al, 2005 ; Venoux et al, 2008 ), indicating that it would be expressed in the BB in ciliated cells. On the other hand, the most recent publication using C. elegans claimed that MAPH-9, an ortholog of MAP9, is localized to the proximal region of the ciliary axoneme adjacent to the base of the cilia, rather than the ciliary BB ( Tran et al, 2023 ). In addition, they also demonstrated that polyglutamylation on MT-axoneme is critical for the MAP9 localization to the ciliary axoneme, as suggested in other MAP proteins ( Boucher et al, 1994 ; Bonnet et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another protein that has been shown to influence doublet formation in C. elegans via polyglutamylation is MAPH-9, the deletion of which reduces the frequency and length of doublets in cilia. However, MAPH-9 is expressed only in ciliated sensory neurons (Tran et al, 2023), not the embryonic cells used in this study.…”
Section: Discussionmentioning
confidence: 99%